2001
DOI: 10.1097/00042737-200109000-00016
|View full text |Cite
|
Sign up to set email alerts
|

The role of gastrointestinal endoscopy in long-distance runners with gastrointestinal symptoms

Abstract: Gastrointestinal symptoms and gastrointestinal mucosal damage are prevalent among long-distance runners. Prior to treatment, gastrointestinal endoscopy should be considered in long-distance runners with gastrointestinal symptoms and/or anaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 39 publications
0
36
0
3
Order By: Relevance
“…In addition, several studies have demonstrated an increased incidence of occult gastrointestinal (GI) blood loss among athletes [8][9][10]. Gross GI blood loss following exercise is less common, although one study reported 16% of runners experienced bloody diarrhea on at least one occasion following strenuous exertion [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies have demonstrated an increased incidence of occult gastrointestinal (GI) blood loss among athletes [8][9][10]. Gross GI blood loss following exercise is less common, although one study reported 16% of runners experienced bloody diarrhea on at least one occasion following strenuous exertion [6].…”
Section: Discussionmentioning
confidence: 99%
“…Gross GI blood loss following exercise is less common, although one study reported 16% of runners experienced bloody diarrhea on at least one occasion following strenuous exertion [6]. Development of ischemic colitis in this population is rare, however [7,10,[11][12][13][14]. Several hypotheses to explain this phenomenon have be proposed.…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio realizado por Choi y Col. 22 en donde 16 corredores de larga distancia fueron sometidos a endoscopia de vías digestivas posterior a una carrera de 20km, así como a colonoscopia en aquellos en quienes se reportó sangre oculta en heces previo o poscarrera, se obtuvo un aumento en prevalencia de daños en la mucosa gástrica desde gastritis, esofagitis o ulcera gástrica (p=0,00005). Aunque los investigadores encontraron sólo 2 sujetos con sangrado intestinal en la exploración macroscópica, 5 presentaron anemia que no se pudo explicar por los daños encontrados en la mucosa GI.…”
Section: Sangrado Gastrointestinalunclassified
“…Sintomas gastrintestinais relacionados ao exercício são comumente encontrados em atletas, como a ocorrência de sangramento gastrintestinal, sobretudo em corredores de longa distância 23,24 .…”
Section: Hemorragia Gastrintestinalunclassified